# Errors in plotting regular function

Suppose we want to define Tanh-function via exponent:

th[x_] := (1 - Exp[-2 x])/(1 + Exp[-2 x]);
FullSimplify[th[x]]

Out[13]= Tanh[x]


Then we define new function:

g[x_] := Sqrt[1 + th[x]]

Simplify[g'[x]]
Out[16]= Sqrt[2] E^(-2 x) (E^(2 x)/(1 + E^(2 x)))^(3/2)


Now try to plot g'[x]:

Plot[g'[x], {x, -60, 60}, PlotRange -> All]


And we got errors:

Power::infy: Infinite expression 1/Sqrt[0.] encountered. >>
Infinity::indet: Indeterminate expression 0. ComplexInfinity encountered. >>
Power::infy: Infinite expression 1/Sqrt[0.] encountered. >>
Infinity::indet: Indeterminate expression 0. ComplexInfinity encountered. >>
Power::infy: Infinite expression 1/Sqrt[0.] encountered. >>
General::stop: Further output of Power::infy will be suppressed during this calculation. >>
Infinity::indet: Indeterminate expression 0. ComplexInfinity encountered. >>
General::stop: Further output of Infinity::indet will be suppressed during this calculation. >>


We have right plot, but why do these errors occur?

It's interesting that when we plot, for example, from -10 to 10, no errors occur.

• Simplify before plotting Plot[Evaluate[g'[x] // Simplify], {x, -60, 60}, PlotRange -> All] – Bob Hanlon Oct 11 '15 at 17:26
• Yes, it works. But the question is - Why do such errors occur? – newt Oct 11 '15 at 17:28
• It is a numerical precision issue at an intermediate step caused by the large exponents to E. Look at Trace[g'[-60.]] compared with Trace[(g'[x] // Simplify) /. x -> -60.] – Bob Hanlon Oct 11 '15 at 18:27
• To help you in answering your own question: what does g'[x] look like before simplifying? – J. M. will be back soon Oct 11 '15 at 18:27

g'[x]


$\frac{\frac{2 e^{-2 x} \left(1-e^{-2 x}\right)}{\left(e^{-2 > x}+1\right)^2}+\frac{2 e^{-2 x}}{e^{-2 x}+1}}{2 \sqrt{\frac{1-e^{-2 > x}}{e^{-2 x}+1}+1}}$

Simplify[g'[x]]


$\sqrt{2} e^{-2 x} \left(\frac{e^{2 x}}{e^{2 x}+1}\right)^{3/2}$

FullSimplify[g'[x]]


$\frac{1}{2} e^{-2 x} (\tanh (x)+1)^{3/2}$

ComplexExpand[g'[x], {x}, TargetFunctions -> Conjugate]


FullSimplify[%]


$-\frac{1}{2} (\tanh (x)-1) \sqrt{\tanh (x)+1}$

Plot[-(1/2) (-1 + Tanh[x]) Sqrt[1 + Tanh[x]], {x, -60, 60}, PlotRange -> All]


Of course, we can also use the built-in functions:

f[x_] := Tanh[x]
Plot[{f[x], f'[x]}, {x, -60, 60}]


f'[x]


$\text{sech}^2(x)$

Plot[Sech[x]^2, {x, -50, 50}, PlotRange -> All]


And we can check:

f'[x] == g'[x]


nope,

$\text{sech}^2(x)=\frac{\frac{2 e^{-2 x} \left(1-e^{-2 x}\right)}{\left(e^{-2 x}+1\right)^2}+\frac{2 e^{-2 x}}{e^{-2 x}+1}}{2 \sqrt{\frac{1-e^{-2 x}}{e^{-2 x}+1}+1}}$

because we'll find roots:

Reduce[f'[x] == a, x]


$c_1\in \mathbb{Z}\land a\neq 0\land \left(x=-\cosh ^{-1}\left(-\frac{1}{\sqrt{a}}\right)+2 i \pi c_1\lor x=\cosh ^{-1}\left(-\frac{1}{\sqrt{a}}\right)+2 i \pi c_1\lor x=-\cosh ^{-1}\left(\frac{1}{\sqrt{a}}\right)+2 i \pi c_1\lor x=\cosh ^{-1}\left(\frac{1}{\sqrt{a}}\right)+2 i \pi c_1\right)$

Reduce[g'[x] == a, x] // Quiet


$c_1\in \mathbb{Z}\land a\neq 0\land \left(\left(0=\frac{1}{2} \left(\sqrt{2} a \text{Root}\left[\text{$\#$1}^3 a^2+3 \text{$\#$1}^2 a^2+\text{$\#$1} \left(3 a^2-2\right)+a^2\&,1\right]-2 \sqrt{\frac{\text{Root}\left[\text{$\#$1}^3 a^2+3 \text{$\#$1}^2 a^2+\text{$\#$1} \left(3 a^2-2\right)+a^2\&,1\right]}{\text{Root}\left[\text{$\#$1}^3 a^2+3 \text{$\#$1}^2 a^2+\text{$\#$1} \left(3 a^2-2\right)+a^2\&,1\right]+1}}+\sqrt{2} a\right)\land x=\frac{1}{2} \left(\log \left(\text{Root}\left[\text{$\#$1}^3 a^2+3 \text{$\#$1}^2 a^2+\text{$\#$1} \left(3 a^2-2\right)+a^2\&,1\right]\right)+2 i \pi c_1\right)\right)\lor \left(0=\frac{1}{2} \left(\sqrt{2} a \text{Root}\left[\text{$\#$1}^3 a^2+3 \text{$\#$1}^2 a^2+\text{$\#$1} \left(3 a^2-2\right)+a^2\&,2\right]-2 \sqrt{\frac{\text{Root}\left[\text{$\#$1}^3 a^2+3 \text{$\#$1}^2 a^2+\text{$\#$1} \left(3 a^2-2\right)+a^2\&,2\right]}{\text{Root}\left[\text{$\#$1}^3 a^2+3 \text{$\#$1}^2 a^2+\text{$\#$1} \left(3 a^2-2\right)+a^2\&,2\right]+1}}+\sqrt{2} a\right)\land x=\frac{1}{2} \left(\log \left(\text{Root}\left[\text{$\#$1}^3 a^2+3 \text{$\#$1}^2 a^2+\text{$\#$1} \left(3 a^2-2\right)+a^2\&,2\right]\right)+2 i \pi c_1\right)\right)\lor \left(0=\frac{1}{2} \left(\sqrt{2} a \text{Root}\left[\text{$\#$1}^3 a^2+3 \text{$\#$1}^2 a^2+\text{$\#$1} \left(3 a^2-2\right)+a^2\&,3\right]-2 \sqrt{\frac{\text{Root}\left[\text{$\#$1}^3 a^2+3 \text{$\#$1}^2 a^2+\text{$\#$1} \left(3 a^2-2\right)+a^2\&,3\right]}{\text{Root}\left[\text{$\#$1}^3 a^2+3 \text{$\#$1}^2 a^2+\text{$\#$1} \left(3 a^2-2\right)+a^2\&,3\right]+1}}+\sqrt{2} a\right)\land x=\frac{1}{2} \left(\log \left(\text{Root}\left[\text{$\#$1}^3 a^2+3 \text{$\#$1}^2 a^2+\text{$\#$1} \left(3 a^2-2\right)+a^2\&,3\right]\right)+2 i \pi c_1\right)\right)\right)$

so, built in is quite smart.